1992
DOI: 10.1007/bf02631038
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal induction of functional differentiation and mammary-derived growth inhibitor expression in cultured mouse mammary gland explants

Abstract: A method for the cultivation of organ explants from abdominal mammary glands of virgin mice has been established. In a serum-free medium containing aldosterone, prolactin, insulin, and cortisol (APIH medium) mammary gland development was documented by lobuloalveolar morphogenesis. The hormonal requirements for in vitro expression of beta-casein and of the mammary-derived growth inhibitor (MDGI) were tested. To this end, a full length cDNA coding for mouse MDGI was prepared displaying strong homologies to a mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 39 publications
3
52
0
Order By: Relevance
“…Importantly, this culture system promotes mammary epithelial cell differentiation as exhibited by the development of lobuloalveoli and the expression of milk proteins, such as ␤-casein (Terry et al, 1977;Mehta et al, 1980;Ganguly et al, 1981;Plaut et al, 1993). The extent of morphological and functional differentiation exhibited by the control mammary glands in our experiments (Figures 2, 5, and 7) are similar to previous reports (Terry et al, 1977;Mehta et al, 1980;Ganguly et al, 1981;Binas et al, 1992;Plaut et al, 1993;Li et al, 1995). In addition to proliferation and differentiation, mammary glands in whole organ culture can be induced to involute, a process mediated by apoptosis (Atwood et al, 1995;Casey et al, 1996), by the removal of the lactogenic hormones and culturing only with insulin (Topper et al, 1975).…”
Section: Discussion Whole Organ Culture To Study Mammary Gland Develosupporting
confidence: 92%
See 1 more Smart Citation
“…Importantly, this culture system promotes mammary epithelial cell differentiation as exhibited by the development of lobuloalveoli and the expression of milk proteins, such as ␤-casein (Terry et al, 1977;Mehta et al, 1980;Ganguly et al, 1981;Plaut et al, 1993). The extent of morphological and functional differentiation exhibited by the control mammary glands in our experiments (Figures 2, 5, and 7) are similar to previous reports (Terry et al, 1977;Mehta et al, 1980;Ganguly et al, 1981;Binas et al, 1992;Plaut et al, 1993;Li et al, 1995). In addition to proliferation and differentiation, mammary glands in whole organ culture can be induced to involute, a process mediated by apoptosis (Atwood et al, 1995;Casey et al, 1996), by the removal of the lactogenic hormones and culturing only with insulin (Topper et al, 1975).…”
Section: Discussion Whole Organ Culture To Study Mammary Gland Develosupporting
confidence: 92%
“…Three-week-old female BALB/c mice (Taconic, Germantown, NY) were primed by daily subcutaneous injections of 50 l of a solution containing 1 g 17␤-estradiol and 1 mg progesterone in peanut oil (EP solution) for nine days (Binas et al, 1992). Briefly, The EP solution was made by dissolving 17␤-estradiol and progesterone in 100% ethanol or pre-warmed peanut oil, respectively.…”
Section: Whole Organ Culture (Woc)mentioning
confidence: 99%
“…MDGI in normal mammary tissue is maximally expressed after cell proliferation has occurred and during the onset of lactation by the differentiated gland (Binas et al, 1992). This suggests a role as a signal for the end of cell division and the completion of tissue differentiation (Spener and Borchers, 1992).…”
Section: Discussionmentioning
confidence: 98%
“…In vitro studies of mouse and bovine MDGI suggest several functions of MDGI on growth and differentiation of mammary gland. These include 1) MDGI specifically inhibit the growth of normal mouse mammary epithelial cells and promote morphological differentiation: the appearance of bulbous alveolar-like structure and formation of fully developed lobuloalveolar structures (16); 2) selective inhibition of endogenous MDGI expression in mouse mammary epithelial cells by use of antisense oligonucleotides suppresses the formation of alveolar-liken structure and impairs ␤-casein synthesis in organ cultures (16); 3) increasing amounts of MDGI mRNA were detected in terminal parts of ducts and lobuloalveolar epithelial cells of differentiated glands and maximally expressed in the terminally differentiated state found just prior to lactation (14); and 4) MDGI expression in mouse mammary epithelium cells is hormonally regulated (41,42). Although a large body of evidence has suggested that MDGI promotes differentiation of mammary epithelial cells in vitro, there is a concern about its role as differentiating factor for mammary gland in vivo.…”
Section: Discussionmentioning
confidence: 99%